Evaluasi Penerapan Sistem Pengendalian Internal atas Penjualan Kredit pada PT. Tri Tehnik Perkasa - Maria Grace Lusiana; Revi Arfamaini (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2022)
In a trading company, one way to deal with competition and increase company revenues is through credit sales. The internal control system will help management increase the effectiveness and efficiency of the company in avoiding the risks posed by credit sales, such as overdue receivables or uncollectible receivables. PT. Tri Tehnik Perkasa is one of the bearing distributors in Surabaya. The purpose of this research is to evaluate the implementation of an internal control system for credit sales at Tri Tehnik Perkasa. This research will be evaluated based on the theory of COSO consisting of five components including control environment, risk assessment, control activities, information and communication, and monitoring. This research was conducted with a qualitative descriptive method, where the researcher described the data by describing the natural conditions that occur in the company. The type of data used is qualitative data obtained from interviews, observation, and documentation techniques. The data source used is primary data. The results showed that PT. Tri Tehnik Perkasa still has not implemented an adequate internal control system. The results can be used to improve the company’s internal control so that in the future there will be no deviations. Keywords: Internal Control System, Credit Sales, System Evaluation, Account Receivables Management